Leadership and the development of the organizational culture of companies. A systematic review - Lievano, Jhony Alexander Barrera; Sanchez, Julian Andres Suarez; López, Sonia Yaneht Santana; Suarez, Víctor Fernando Vergel (Edelweiss Applied Science and Technology, 2025)
This research examines the relationship between organizational culture and leadership, highlighting how the latter influences the development of various dynamics within companies and organizations across different sectors and geographic regions worldwide. The study was conducted through a literature review using systematic methods to collect data. A total of 72 relevant documents were analyzed and selected from the Scopus database based on specific criteria such as the period of publication (2015–2023), thematic relevance, and document type. The research process was structured around three key questions: How does leadership influence the development of organizational culture in companies? What are the main types of leadership employed in fostering organizational culture within companies? What are the primary contributions of research regarding the influence of leadership on the development of organizational culture in companies? One of the key findings highlights the significance of leadership strategies that incorporate aspects such as talent development, effective communication, shared responsibility, team strengthening, and the integration of values related to competitiveness and environmental sustainability. Additionally, various leadership styles identified in the reviewed documents and their impact on different organizations are discussed. The study also reveals significant contributions from leadership research regarding the development of capabilities and key factors.